OPTIMALISASI PEMILIHAN CALON PENERIMA BANTUAN BEASISWA PIP DENGAN MENGGUNAKAN METODE TOPSIS (Studi Kasus : SD Negeri Plemahan 2, Kec. Sumobito) - Nurnanda Yudha Prawira; Iftitaahul Mufarrihah; Ahmad Heru Mujianto; Ginanjar Setyo Permadi (Inovate, 2025)
The Indonesia Pintar Program at SD Negeri Plemahan 2, Sumobito District, utilizes the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method. TOPSIS was selected due to its capability to offer optimal solutions by assessing how close alternatives are to the ideal solution.This study created a web-based information system to streamline the selection process of scholarship recipients. The system integrates various relevant criteria to assess the eligibility of candidates, such as economic conditions, academic performance, and other supporting factors. By applying the TOPSIS method, this system can offer more objective and structured recommendations in determining aid recipients.The study's results indicate that the information system not only enhances efficiency in the selection process but also provides better transparency and accuracy in decision-making. The school scholarship aid is granted to students in grades I-VI at SD Negeri Plemahan 2. The final TOPSIS calculation yielded a highest score of 0.916044465, selecting the students who correspond with the recipients of the school scholarship aid for the 2023/2024 academic year. Keywords: PIP, Information System, TOPSIS